Analisa Faktor Yang Mempengaruhi Perilaku Seksual Pranikah Pada Remaja Di Kelompok Umat Basis (KUB) St. Yakobus Rasul Naimata Kota Kupang Provinsi Nusa Tenggara Timur Tahun 2020 - Yuliana Dafroyati; Ririn Widyastuti (FORIKES, 2021)
Adolescence is a period of storm and stress because adolescents experience many challenges both from themselves (biopsychosocial factors) and the environment (environmental factors). Riskesdas data in 2018 showed that there was 0.3 percent of adolescents aged 10-14 years old and 3.7 percent aged 15-19 years old currently consume alcoholic drinks. The proportion age of first-time smoking was 42.8 percent of adolescents aged 10-14 years old and 54.2 percent of adolescents aged 15-19 years. 64.8 percent of adolescents do not have knowledge about HIV / AIDS. The complexities of health problems in adolescents require comprehensive and integrated solutions. The research objective was to analyze factors that influence premarital sexual behavior among adolescents in the basic ecclesial community of St. Joseph the Prophet Catholic Church, Kupang City, East Nusa Tenggara Province in 2020. This type of research is a descriptive-analytic study with a cross-sectional approach. The population and targets in this study were all youths of basic ecclesial community of St. Joseph the Prophet Catholic Church, Naimata, Kupang City, which in total were 100 adolescents. The data analysis technique used univariate and bivariate analysis using Spearman's Rho correlation test with α